La hora de la estrella - Lispector, Clarice (Biblioteca Clarice Lispector, 2015)
In a haunting psychological tale of despair and freedom, Macabea is ugly, underfed, sickly, and unloved yet she fascinates Rodrigo because she is unaware of how unhappy she should be.